Prevalensi dan Faktor Resiko Anemia pada Wanita - Oksita Asri Widyayanti; Epsi Marwati; Assha Luthfianie Alifah; Utami Pratyastiti Setyarini (Jurnal Nurse, 2021)
Anemia is a common medical condition throughout the world, with a high prevalence in women. This study aims to evaluate the prevalence of anemia and identify risk factors associated with this condition in a female population. The research method involves a cross-sectional survey involving a sample of adult women from various social, economic and demographic backgrounds. Data was collected using a questionnaire that included demographic information, nutritional status, health history and eating patterns. Statistical analysis was performed to determine the prevalence of anemia and identify significant risk factors. The results showed that the prevalence of anemia in the female population is high, with the main risk factors including iron deficiency, pregnancy, heavy menstruation, and lack of adequate nutritional intake. These findings highlight the importance of targeted interventions to prevent and manage anemia in women, including nutrition education, iron supplementation, and improved access to reproductive health services. Further research is needed to better understand the complexity of factors involved in the prevalence of anemia in women and develop more effective strategies for its prevention and treatment.